Validation of an Instrument for Strategies to Strengthen Learning - Ramos-Estrada, Dora Yolanda (2020)
The purpose of this study was to validate an instrument aimed to evaluate the strategies that teachers use to strengthen learning. The study was conduced with a quantitative, non-experimental, instrumental type approach. In the study, 210 teachers participated and they were from different educational institutions. The instrument used was “Strategies to Strengthen Learning” of Mitchell (2015a). The results of the exploratory factor analysis technique validated five subscales related to the strategies, which are the following: learning context, teaching strategies, behavioral strategies, interinstitutional cooperation strategies and resource strategies for learning. This study contributes to the advancement of scientific knowledge on the analysis of psychometric properties of instruments, and will serve as a reference in subsequent studies that seek to evaluate teacher’s teaching strategies.